If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(2x-3)+2=-8
We move all terms to the left:
(2x-3)+2-(-8)=0
We add all the numbers together, and all the variables
(2x-3)+10=0
We get rid of parentheses
2x-3+10=0
We add all the numbers together, and all the variables
2x+7=0
We move all terms containing x to the left, all other terms to the right
2x=-7
x=-7/2
x=-3+1/2
| (2x-3)+2=8 | | 2x-3+2=8 | | 6*3x=54 | | 9p-4=8p+38 | | x/192=32 | | |9p-4|=|8p+38| | | -13+57=-4(x+3) | | 12=7x-4 | | 9x-1+5=10 | | |9x-1|+5=10 | | 11x^2+21=7 | | 3n=15-2n | | 11x^+22=7 | | x-23=-9 | | m+7+7=17 | | m+8+3=-30 | | m+8+3=30 | | x+9=10x-15 | | 577x-27-566x+64-37=33 | | x-9=-10x-15 | | 9(x-1)-6=4x+5(-3+x) | | -8+z=2 | | 4(6n-1)+8=6(4n+6) | | 5÷7x+9=78 | | 18-13=1/2a+3/4a+5/8a | | (2+-1)(t+5)=0 | | 2+-1)(t+5)=0 | | (0.75-x)^2÷2x=0.11 | | 0.02(x-1)=-12 | | |x-6|=25 | | 3x2+x=x+243 | | 0=-2x^2+2x |